Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1080/17470218.2011.554990
|View full text |Cite
|
Sign up to set email alerts
|

Supervised versus Unsupervised Categorization: Two Sides of the Same Coin?

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 54 publications
(233 reference statements)
1
14
0
Order By: Relevance
“…Both models are based on the same idea, comparing within-category similarity to between-category similarity, with 'better' (easier to learn and more intuitive, cf. Pothos, Edwards & Perlman, 2011a) …”
Section: Methodsmentioning
confidence: 99%
“…Both models are based on the same idea, comparing within-category similarity to between-category similarity, with 'better' (easier to learn and more intuitive, cf. Pothos, Edwards & Perlman, 2011a) …”
Section: Methodsmentioning
confidence: 99%
“…But instead we found that these contextual factors modulated the categories that people used, and their social coherence. Thus, while our findings cannot tell us precisely which dimensions people selected for sorting, they do suggest that the dimensions that people choose during unsupervised categorization are somewhat flexible, in ways that are by definition independent of error‐based feedback (Goldstone, ; Pothos, Edwards, et al, ), and conversely are at least partially dependent on factors such as language and the context (or goal) of sorting. We note however that our participants were limited to categorizing the items into two groups only (i.e., rather than choosing their own number of categories; Pothos, Edwards, et al, ).…”
Section: Discussionmentioning
confidence: 58%
“…Thus, while our findings cannot tell us precisely which dimensions people selected for sorting, they do suggest that the dimensions that people choose during unsupervised categorization are somewhat flexible, in ways that are by definition independent of error‐based feedback (Goldstone, ; Pothos, Edwards, et al, ), and conversely are at least partially dependent on factors such as language and the context (or goal) of sorting. We note however that our participants were limited to categorizing the items into two groups only (i.e., rather than choosing their own number of categories; Pothos, Edwards, et al, ). In future work, it would be beneficial to examine the effects of novel labels alongside contextual factors (such as labels and the context of sorting) on category flexibility and social coherence when sorters are free to determine their own number of categories.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations